2022
DOI: 10.1002/ece3.9591
|View full text |Cite
|
Sign up to set email alerts
|

A new GTSeq resource to facilitate multijurisdictional research and management of walleye Sander vitreus

Abstract: Conservation and management professionals often work across jurisdictional boundaries to identify broad ecological patterns. These collaborations help to protect populations whose distributions span political borders. One common limitation to multijurisdictional collaboration is consistency in data recording and reporting. This limitation can impact genetic research, which relies on data about specific markers in an organism's genome. Incomplete overlap of markers between separate studies can prevent direct co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Microhaplotypes have shown promise in several fisheries‐related studies including pedigree inference and population assignment. Inclusion of microhaplotype data can increase power for identifying kin relationships (Baetscher et al., 2018; Delomas & Campbell, 2022; Euclide et al., 2022) and fewer microhaplotypes are necessary to obtain equivalent levels of accuracy with parentage analysis relative to bi‐allelic SNPs (May et al., 2020). Similarly, added variability associated with microhaplotypes has the potential to differentiate closely‐related populations, resulting in increased accuracy in GSI assignments (Euclide et al., 2021; McKinney et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Microhaplotypes have shown promise in several fisheries‐related studies including pedigree inference and population assignment. Inclusion of microhaplotype data can increase power for identifying kin relationships (Baetscher et al., 2018; Delomas & Campbell, 2022; Euclide et al., 2022) and fewer microhaplotypes are necessary to obtain equivalent levels of accuracy with parentage analysis relative to bi‐allelic SNPs (May et al., 2020). Similarly, added variability associated with microhaplotypes has the potential to differentiate closely‐related populations, resulting in increased accuracy in GSI assignments (Euclide et al., 2021; McKinney et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Using microsatellite DNA markers, Stepien et al [10,11] showed differentiation among populations of Walleye from watersheds across the Laurentian Great Lakes, Lake Winnipeg (MB, Canada), upper Mississippi River, Ohio River, and Mobile Bay drainage. Using SNP markers, Euclide et al [12] showed differentiation among Walleye populations in the Great Lakes region.…”
Section: Introductionmentioning
confidence: 99%